Squamous cell carcinoma of the kidney in a patient with staghorn calculi (Indian Journal of Case Reports, 2019)
Primary squamous cell carcinoma of the renal parenchyma is an extremely rare entity. The diagnosis of squamous cell carcinoma of the renal pelvis is usually unsuspected due to the rarity and inconclusive clinical and radiological features. The insidious onset of symptom and lack of any pathognomonic sign leads to delay in the diagnosis and subsequent treatment, resulting in grave prognosis for these patients. Here, we present a case of incidentally detected renal squamous cell carcinoma in a 71-year-old male with a staghorn calculus and Xanthogranulomatous pyelonephritis. The patient was treated with radical nephrectomy.